Asymmetric Total Synthesis of Hispidanin A. Issue 21 (20th April 2017) - Deng, Heping; Cao, Wei; Liu, Rong; Zhang, Yanhui; Liu, Bo
Abstract: Asymmetric total synthesis of the dimeric diterpenoid hispidanin A was accomplished by non‐catalytic Diels–Alder cycloaddition at room temperature. The synthesis relies on iron‐catalyzed coupling to construct a Z ‐configured trisubstituted alkene, an iron‐catalyzed radical cascade to generate a labdane‐type diene, and both Yamamoto cationic polyene cyclization and palladium‐catalyzed Stille coupling to generate a totarane‐type dienophile. Abstract : Radical is radical : Asymmetric total synthesis of a dimeric diterpenoid, hispidanin A, has been accomplished through spontaneous [4+2] cycloaddition without catalysis at room temperature. Construction of the diene fragment features a designed radical polyene cyclization triggered by metal‐catalyzed hydrogen atom transfer, while subsequent asymmetric cationic polyene cyclization generates the dienophile fragment.